FACTORS AFFECTING NON-PERFORMING LOANS PT. BPR ARTO MORO SEMARANG - Darmawan Darmawan; Arini Novandalina; Tossy Aryanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Credit is a high-risk business activity in which uncollectible credit occurs for various reasons. Many debtors who pay credit must pay attention to the provisions of interest rates, time periods, and several provisions that make debtors object to paying their credit. The purpose of this study is to determine three factors from debtors that cause problem loans to become bad loans. Three debtor factors that cause bad credit are debtor character, business conditions (most BKK debtors are MSME entrepreneurs from small to large scale), and managerial ability (in managing their own business). This type of research is explanatory research with a total sample of 51 respondents to customers of PT. BPR Arto Moro Semarang, located in Semarang, has experienced bad credit from 2018-2022. The results showed that only Business Conditions were accepted, and had a positive effect of 10.354 and a sig value > 0.05. Meanwhile, Managerial Character and Ability have no influence and significance on Bad Debt. It is recommended for the bank to do more internal analysis of prospective borrowers in providing credit financing. Researching the current and future conditions of the debtor's business, as well as paying attention to the debtor's managerial ability in running the business or business.